Analysis of Student Ability in Using the AutoCAD Program in Civil Engineering Study Program Faculty of Engineering University Muhammadiyah of Aceh - Ira Dama Yanti; Maimunah; Manovri Yeni (LPPM Universitas Malikussaleh, 2022)
Every world of business and world of work (WBWW) needs human resources who can master and learn science and technology, which are continuously transforming. Civil engineering jobs include designing, constructing, maintaining, and repairing buildings. Auto Computer Aided Design (AutoCAD) technology software is very useful for civil engineering work when designing buildings. All WBWW in the field of civil engineering uses AutoCAD software when designing engineering, so human resources working in this field must be able to master AutoCAD software. On this basis, graduates of civil engineering are required to be able to master and operate application programs in the field of engineering. In the field of construction, human resources who are proficient in using AutoCAD are much needed. The Faculty of Engineering (FT) at the University Muhammadiyah of Aceh (UNMUHA) implements the use of AutoCAD in its curriculum. AutoCAD is one of the tools that supports the skills and development of the Civil Buildings Drawing (CBD) II Course. AutoCAD is an application program used for drawing, designing drawings, and testing materials. This research is to assess the frequency of the levels of mastery, skill, motivation, and discipline of Civil Engineering Study Program students at FT UNMUHA. The sampling technique used was purposive sampling, which is a sampling technique with the consideration that the respondents in this study were students of the Civil Engineering Study Program at FT UNMUHA who were active in the Even Semester of the 2021-2022 Academic Year and who programmed CBD II Course in their Study Plan Card (SPC), totaling 74 respondents. The results of this study indicate that students of the Civil Engineering Study Program at FT UNMUHA have high levels of mastery, interest, motivation, and discipline in completing drawing assignments using the AutoCAD application in the CBD II Course in the even semester of the 2021–2022 academic year.